ANALISIS KEBERLANJUTAN PRAKTIK PERTANIAN SAYURAN ORGANIK DI KECAMATAN PARONGPONG KABUPATEN BANDUNG BARAT - Andriani, Rani; Kusumo, Budi; Charina, Anne (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
Increased demand for organic vegetables in Indonesia proves that business opportunities of organic vegetables are still wide. However, the number of farmers who cultivate organic vegetables is very limited. This is the basis of thinking about the sustainability of organic vegetable farming practices in Cisarua Subdistrict of West Bandung Regency. This research aimed to analyze the sustainability of organic vegetable farming in Cisarua Subdistrict, in terms of ecological, economic, social, technology and infrastructure, and institutional dimensions. This research was a qualitative research. Respondents in this study were all organic vegetable farmers in Cisarua Subdistrict that required 8 people. The data were analyzed to measure the sustainability status by using multidimensional scaling (MDS) analysis. The results showed that the ecological, economic, technology and infrastructure, and institutional dimensions had sustainable status, while that of the social dimension less sustainable. These results indicate that in the development of organic vegetable farming, farmers need support from agricultural extension institution association, and marketing of agricultural products.